Characterization of a Vaginal Limosilactobacillus Strain Producing Anti-Virulence Postbiotics: A Potential Probiotic Candidate - Tsvetelina Paunova-Krasteva; Petya D. Dimitrova; Dayana Borisova; Lili Dobreva; Nikoleta Atanasova; Svetla Danova (Fermentation)
The search for probiotics to help limit antibiotic resistance is a major scientific challenge. The exploration of Lactobacillus postbiotics represents a promising approach to prevent pathogen invasion. With this aim, Limosilactobacillus fermentum Lf53, with a broad-spectrum of antagonistic activity, was characterized as a candidate probiotic strain with promising transit tolerance and broad spectrum of activity. A study on growth and postbiotic production in modified MRS broth with different carbohydrates and its vegan variant was carried out. This study presents a comprehensive approach to characterizing the anti-virulence properties of postbiotics derived from Lf53. The promising antibacterial, antibiofilm, and anti-quorum sensing activities of the cell-free supernatants (CFS) were assessed as part of the probiotic’s barrier mechanisms. Biofilm inhibition of P. aeruginosa revealed remarkable suppressive effects exerted by the three tested postbiotics, two of which (nCFS and aCFS) exhibited over 50% inhibition and more than 60% for lysates. The postbiotics’ influence on the production of violacein and pyocyanin pigments of Chromobacterium violaceum and Pseudomonas aeruginosa, which are markers for quorum sensing, highlighted their potential in regulating pathogenic mechanisms. The Lf53 lysates showed the most significant inhibition of violacein production across multiple assays, showing 29.8% reduction. Regarding pyocyanin suppression, the postbiotics also demonstrated strong activity. These are the first reported data on complex postbiotics (metabiotics and parabiotics) demonstrating their potential as anti-virulence agents to help combat pathogens associated with antibiotic-resistant infections.